Optimized Conditions for Flavonoid Extraction from Pomelo Peel Byproducts under Enzyme- and Ultrasound-Assisted Extraction Using Response Surface Methodology - Mai Nguyen Tram Anh; Pham Van Hung; Nguyen Thi Lan Phi (Journal of Food Quality)
Pomelo (Citrus maxima (Burm.) Merrill) peel, which has been considered as a byproduct, is a potential source of flavonoids. In this study, the extraction conditions of total flavonoids from peels of Da Xanh pomelo were optimized using the response surface methodology with the Box–Behnken design. The combination of two novel extraction methods, including enzyme-assisted and ultrasound-assisted extractions, was used for the optimization. The results indicated that the optimal extraction condition was a liquid-to-solid ratio of 142.99 mL/g, enzyme concentration of 3.45%, and the time of 65.23 min for incubation and of 69.26 min for sonication treatment. Total phenolic and total flavonoid contents of the pomelo peel extracts, under optimal condition of the combined method (16.79 mg GAE/g and 10.69 mg RE/g, respectively), were significantly higher than those of the conventional method (6.58 mg GAE/g and 2.42 mg RE/g, respectively). The naringin and hesperidin contents of extracts under optimal condition increased by 5.70% and 1.20%, respectively, compared to the extracts under the conventional method.